1984
DOI: 10.1042/bj2240389
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the complement-component-C3b-binding site and the cofactor activity for factor I in the 38kDa tryptic fragment of factor H

Abstract: Trypsin treatment of human factor H (H160) [enzyme/substrate ratio 1:100 (w/w), 30 min, 37 degrees C] generated a 38 kDa (H38) and a 142 kDa (H142) fragment linked by disulphide bonds (H38/142). The fragments were purified by reduction with 2-mercapto-ethanol, gel filtration on a Sephadex G-200 column and affinity chromatography with monoclonal anti-(factor H) antibody coupled to Sepharose 4B. This monoclonal antibody bound to a site in the 38 kDa fragment. To localize the C3b binding site in factor H we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
73
0
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 19 publications
0
73
0
1
Order By: Relevance
“…SCRs 1-10 and 16 -20 of Factor H are believed to contain the binding site(s) for C3b, and decay-accelerating and cofactor activities have been localized to SCR 1-5 ( Fig. 9) (20,(23)(24)(25)(26)(27)(28).…”
Section: Table III Amino Acid Homology Of Hplc-purified Peptides To Tmentioning
confidence: 99%
“…SCRs 1-10 and 16 -20 of Factor H are believed to contain the binding site(s) for C3b, and decay-accelerating and cofactor activities have been localized to SCR 1-5 ( Fig. 9) (20,(23)(24)(25)(26)(27)(28).…”
Section: Table III Amino Acid Homology Of Hplc-purified Peptides To Tmentioning
confidence: 99%
“…It has been suggested that a total of three C3b-binding sites exist on fH. One has been located to the amino-terminal tryptic fragment (SCR1-6a) (33,34) and further mapped by functional assays to SCRs 1-4 (35)(36)(37). The other two binding sites have not yet been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…This 150 kDa glycoprotein is composed of 20 complement control protein (CCP) domains. The N-terminal part of the molecule (CCPs 1-4) is responsible for its complement regulatory activity (Alsenz et al, 1984;Kühn et al, 1995). FH has multiple binding sites for C3b, located within CCPs 1-4, CCPs 12-15 and CCPs 19-20 (Sharma and Pangburn, 1996;Jokiranta et al, 2000), and for heparin, located in CCP7, CCP9, CCPs 12-14, and CCPs 19-20 (Pangburn et al, 1991;Blackmore et al, 1996Blackmore et al, , 1998Ormsby et al, 2006).…”
Section: Introductionmentioning
confidence: 99%